Downregulation of PGC-1α Prevents the Beneficial Effect of EET-Heme Oxygenase-1 on Mitochondrial Integrity and Associated Metabolic Function in Obese Mice. (20th December 2016) - Singh, Shailendra P.; Bellner, Lars; Vanella, Luca; Cao, Jian; Falck, John R.; Kappas, Attallah; Abraham, Nader G.
Abstract : Background/Objectives . Obesity and metabolic syndrome and associated adiposity are a systemic condition characterized by increased mitochondrial dysfunction, inflammation, and inhibition of antioxidant genes, HO-1, and EETs levels. We postulate that EETs attenuate adiposity by stimulating mitochondrial function and induction of HO-1 via activation of PGC-1 α in adipose and hepatic tissue. Methods . Cultured murine adipocytes and mice fed a high fat (HF) diet were used to assess the functional relationship among EETs, PGC-1 α, HO-1, and mitochondrial signaling using an EET-agonist (EET-A) and PGC-1 α -deficient cells and mice using lentiviral PGC-1 α (sh). Results . EET-A is a potent inducer of PGC-1 α, HO-1, mitochondrial biogenesis (cytochrome oxidase subunits 1 and 4 and SIRT3), fusion proteins (Mfn1 / 2 and OPA1) and fission proteins (DRP1 and FIS1) (p < 0.05 ), fasting glucose, BW, and blood pressure. These beneficial effects were prevented by administration of lenti-PGC-1 α (sh). EET-A administration prevented HF diet induced mitochondrial and dysfunction in adipose tissue and restored VO2 effects that were abrogated in PGC-1 α -deficient mice. Conclusion . EET is identified as an upstream positive regulator of PGC-1 α that leads to increased HO-1, decreased BW and fasting blood glucose and increased insulin receptor phosphorylation, that is, increased insulin sensitivity and mitochondrial integrity, and possible use of EET-agonist for treatment of obesity and metabolic syndrome.